One-pot-like facile synthesis of YBa2Cu3O7-δ superconducting ceramic: Using PVP to obtain a precursor solution in two steps - Rotta, Maycon [UNESP]; Motta, Maycon; Pessoa, Alexsander Lourenço [UNESP]; Carvalho, Claudio Luiz [UNESP]; Deimling, Cesar Vanderlei; Lisboa-Filho, Paulo Noronha [UNESP]; Ortiz, Wilson Aires; Zadorosny, Rafael [UNESP] (Elsevier, 2020)
There are a variety of chemical routes used to produce advanced ceramic materials. The sol-gel-like methods are widely applied since the final samples present high stoichiometric and grain size homogeneity. However, with the search for sustainable practices, researchers have been worked in the so-called one-pot synthesis, where all the chemical reactions occur in a single vessel with low residue production. Thus, in this work, we used a one-pot-like synthesis adapted to produce YBa2Cu3O7-δ superconducting ceramic samples. One shows that, in two main steps, a polymer solution is prepared in a few hours, and after heat treatments, a single-phase material is obtained. It is shown that the one-pot-like samples can present a higher diamagnetic signal in comparison with specimens prepared by the well-known Pechini Method. With this work, we show that there are alternative routes to produce advanced ceramics with simple and secure methods, if we compare, e.g., with trifluoroacetate routes.
Keywords: Acetates; Ceramic; One-pot; Sol-gel; Superconductor